Improving jump training based on body difficulty requirements in gymnastics - Udalova M.A. ,; Zyukin A.V. ,; Kiryanova L.A. ,; Bystrova I.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to increase the level of non‑objective training according to the regulations of Body Difficulties in rhythmic gymnastics by introducing a set of means of jumping training of gymnasts. Results and conclusions. At the first stage, the level of jumping training of gymnasts was tested. At the second stage, a set of means of jumping training was introduced into the training process, including jumping with a rope with and without weights, as well as jumps in accordance with the technical regulations of FIG. Results and conclusions. It was found that under the influence of the developed set of means of jumping training, a new functional state of gymnasts is formed, providing the greatest increase in the indicators of special endurance, speed, strength and speed‑strength qualities of gymnasts in performing jumps over a rope in accordance with the rules of competitions in rhythmic gymnastics.